The sky and sustainable tourism development: a case study of a Dark Sky Reserve implementation in Alqueva - Rodrigues, Áurea (2021)
This paper shows the development of a tourism product in a destination that uses the night sky as its main source of attraction. Using this innovative product has helped to create a distinctive image, which is likely to attract a more diverse range of visitors and has assisted in improving economic, social and environmental sustainability. First, we present an overview about sustainable tourism and the sky as a tourism resource followed by a case study, in Portugal, that illustrates the potential of Dark Sky activities for tourism development in rural regions.